"Ideal" parathyroid hormone in erythropoietin‐stimulating agents‐resistant anemia. Issue 1 (24th November 2021) - Ashraf, Bilal; Bat, Taha; Weinberg, Olga K.; Moe, Orson W.; Ibrahim, Ibrahim
Abstract: Erythropoietin‐stimulating agents (ESAs) have revolutionized anemia treatment in end‐stage renal disease (ESRD), but ESA resistance is increasingly identified. Secondary hyperparathyroidism (SHP) is one cause of ESA resistance. We describe a patient with ESA‐resistant, transfusion‐dependent anemia and mild SHP with remodeling and reticulin fibrosis on bone marrow biopsy, all of which resolved with stricter SHP management. We identified 64 patients with anemia, ESRD, and bone marrow biopsy. The parathyroid hormone (PTH) range for bony remodeling was 183–16, 161.9 pg/ml versus 90.8–3283 pg/ml. The PTH range for fibrotic changes was 183–2487 pg/ml versus 90.8–16, 161.9 pg/ml. We found no clear PTH range predictive for bone marrow changes.